Pengembangan Usaha pada Warung Kopi Lima Malang Dengan BostonConsulting Group (BCG) Matrix - Faizal Syahrul; SYAHRUL, FAIZAL (J-Mabes: Jurnal Manajemen, Akuntansi, Bisnis dan Studi Ekonomi Syariah, 2024)
Coffee is a beverage that has long been consumed by Indonesians. One of the coffee based business that has high competition is the coffee beverage business. Business competition that occurs in this coffee sector makes business owners need to apply strategic management in order to compete with other business subjects and develop businesses, Warung Kopi Lima Malang is one of them. The purpose of this study is to determine the position of Warung Kopi Lima in the BCG matrix to formulate strategies that can be used as well as to find out examples of implementing strategies resulted from the matrix recommendations. This research uses a descriptive quantitative approach with document study data collection. The products observed were black coffee, coffee milk and iced coffee milk. The data analysis method used is the BCG (Boston Consulting Group) Matrix. This study shows that black coffee has a question mark position with a market growth of 0.08% and a relative market share of 0.17. Coffee Milk products have a dog position with a market growth of -15.87% and a market share of 0.47. The iced coffee milk product has a cash cow position with a market growth of -30.42% and a market share of 1.18. Based on the BCG matrix, alternative strategies that can be used in black coffee are market penetration, market development, product development or divestment. In coffee milk products are liquidation, divestment, or pruning through shrinkage. In iced milk coffee is product development or diversification.